MEMBANGUN KARAKTER ANAK MELALUI PERMAINAN AMPAR-AMPAR PISANG BERBASIS KEARIFAN LOKAL DENGAN METODE SARISWARA - Indah Purnama Sari, Dyan; Setiani, Mita; Asysyifa Mugnianingsih , Nuuri; Agnes Ratna Ramadhan, Sylvia; Afiani, Annisa; Putri, Prisilia (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2021)
The paper was created to describe the benefits of traditional ampar-ampar pisang games based on local wisdom in building children's character with Sariswara method as the main foundation. The background of this writing is due to the change in children's play activities today, where children now prefer to play digital games and are identical to the use of modern technology such as video games and online games. As a result, traditional games are now beginning to be forgotten and become unfamiliar among today's children. Furthermore, the level of addiction to modern games in children is also increasingly crazy, thus affecting the children's life habits and behaviors. This paper is based on a literature study that outlines the various impacts that occur in children when addicted to playing games that can result in the character that will be formed in the child. This paper also compares the influence of modern games with traditional games based on local wisdom with Sariswara methods on children's characters. By restoring the role and function of traditional children's games such as banana hooks as children's games, today can be a solution to create a generation of people with superior character.